Website-based Library Information System at SMK Muhammadiyah Adiwerna - Muhamad Bakhar; Muchamad Sobri Sungkar; Ulil Albab (SEULANGA SYSTEM PUBLISHER, 2025)
This study aims to design and develop a web-based library information system to enhance the efficiency and accuracy of library management at SMK Muhammadiyah Adiwerna, Tegal Regency. The main issues previously encountered were error-prone manual recording, slow data retrieval, and difficulties in generating reports. The system was designed using the waterfall method with PHP as the programming language and MySQL as the database. The key features developed include book borrowing and returning records, book and member data management, as well as customized dashboard displays for administrators and users (teachers/students). System testing was conducted using the black box testing method on the main functionalities. The test results indicate that the system operates in accordance with the specifications and user requirements. This system has successfully improved the efficiency, speed, and ease of access to library information.